Factors Influencing the Educational Achievements of Students in Single-Parent Mother-Headed Families: A Critical Study on Selected Secondary Schools in Sri Lanka - Jemeela Jalaldeen; Mohammed Ghous Mohammed Insaf (Indonesian Educational Research Journal, 2025)
The family unit is a crucial social agent, and the issues may negatively affect students' education. This study aims to identify the factors that influence the education of students from single-parent, mother-led families in selected secondary schools within the Kegalle Educational Zone. The survey method was utilized in this research, with the questionnaire serving as the primary source of data collection for respondents. A sample size of 30 participants was chosen using a combination of simple random sampling and purposive sampling. The data was analyzed using percentage statistical methods to draw meaningful conclusions. The findings of this study indicate that low educational attainment among single mothers, combined with financial hardships and limited resources, negatively impacts their children's academic performance. Addressing these challenges through targeted support and resource provision is crucial to ensuring equitable educational opportunities for all students.